Organic amendments affect soil parameters in two long-term rice-wheat experiments - Tirol-Padre, A.; Ladha, J.K.; Regmi, A.P.; Bhandari, A.L.; Inubushi, K. (Wiley, 2007)
The impacts of continuous applications of an organic manure (farmyard manure [FYM], green manure [GM], and wheat straw [WS]) combined with inorganic fertilizers (N, P, and K) on soil parameters and productivity of rice (Oryza sativa L.)–wheat (Triticum aestivum L.) systems were investigated in two long‐term experiments under conventional tillage in Ludhiana, India, and Bhairahawa, Nepal. Changes in total and labile soil C and N, and microbiological parameters relative to unfertilized and inorganically fertilized controls were measured. Organic amendments had positive but variable effects. In Ludhiana, FYM application increased total C and N, permanganate‐oxidizable C, and hot‐water‐extractable C (HWEC) by 40 to 70% relative to the control after 20 yr and maintained HWEC and total N with time. In the other treatments, HWEC and total N showed declining trends with time, whereas total C increased by 17% on average. In Bhairahawa, although total organic C and N increased with organic amendments after 15 yr, HWEC did not. Increases in C and N, respectively, as fractions of the applied organic fertilizers were 11 to 23 and 37 to 39% from FYM, 4 to 21 and 19 to 41% from GM, and 3 and 24% from WS. The FYM improved available P, cation exchange capacity, potential mineralizable N, and dehydrogenase activity, but microbial biomass C, basal respiration, flush of CO2 after rewetting dried soil, and metabolic quotient remained unchanged. The current practice of inorganic fertilization alone cannot maintain the soil quality needed to sustain crop productivity. Amounts of organic manures to supplement inorganic fertilizers must be optimized to increase C and N accumulations in the soil without negative effects on crop yield.